Malnutrition drives infection susceptibility and dysregulated myelopoiesis that persists after refeeding intervention - Alisa Sukhina; Clemence Queriault; Saptarshi Roy; Elise Hall; Kelly Rome; Muskaan Aggarwal; Elizabeth Nunn; Ashley Weiss; Janet Nguyen; F Chris Bennett; Will Bailis (eLife)
Undernutrition remains a major global health crisis, with nearly 1 billion people experiencing severe food insecurity. Malnourished individuals are especially vulnerable to infectious diseases, which is the leading cause of morbidity and mortality for this population. Despite the known link between undernutrition and infection susceptibility, the mechanisms remain poorly understood, and it is unclear whether refeeding can reverse nutritionally acquired immunodeficiency. Here, we investigate how malnutrition leads to immune dysfunction and the ability of refeeding to repair it. Malnourished mice show an inability to control sublethal Listeria monocytogenes infection, reduced immune cell function and expansion, and early contraction before pathogen clearance. Myelopoiesis is particularly affected, with fewer neutrophils and monocytes present both before and after infection in malnourished mice. While refeeding restores body mass, lymphoid organ cellularity, and T cell responses, refed mice remain susceptible to Listeria infection, revealing that recovery from lymphoid atrophy alone is not sufficient to restore protective immunity. Accordingly, peripheral neutrophils and monocytes fail to fully recover, and emergency myelopoiesis remains impaired in refed animals. Altogether, this work identifies dysregulated myelopoiesis as a link between prior nutritional state and immunocompetency, indicating that food scarcity is an immunologic risk factor, even after nutritional recovery.